Cultural considerations in the assessment of sensitivity in low-income caregivers in Ethiopia - Spinelli, Maria; Preti, Emanuele; Kassa, Temsegen Tadele; Asale, Moges Ayele; Goshu, Mulat Asnake; Tsega, Tigist Wuhib; Gezie, Abebaw Minaye; Fasolo, Mirco; Mesman, Judi (Frontiers in Psychology, 2023)
Background Caregiver sensitivity is associated with positive child outcomes, and improving sensitivity is often the aim of parenting-directed interventions. However, sensitivity was conceptualized in Western cultures, and its application in populations with different backgrounds is still limited. Objective This study aimed to foster a contextualized cultural understanding of the meaning and nature of sensitivity by assessing the possibility of evaluating sensitivity in a low-income population living in Ethiopia and describing the nature of (in)sensitive parenting. Moreover, the associations between sensitivity and discipline, the quality of the environment, and individual characteristics were explored. Methods Parental sensitivity was coded on naturalistic video-recorded observations of free interactions between 25 female primary caregivers and their children. Caregivers completed questionnaires on discipline strategies and the level of satisfaction with the environment (access to basic needs, quality of house condition, community and family support, quality of learning opportunities, and working conditions). Results The assessment of sensitivity in this population was possible, with caregivers showing the full range of sensitivity levels. A description of manifestations of sensitivity in this population is provided. A K-means cluster analysis evidenced that high sensitivity was associated with high satisfaction regarding housing conditions and family environment. No association between sensitivity and discipline emerged. Conclusion The findings show the feasibility of assessing sensitivity in this sample. The descriptions of observed behaviors contribute to understanding culturally specific aspects of sensitivity to consider when assessing sensitivity in similar populations. The study provides considerations and guidelines to inform the structure of culturally-based interventions to promote sensitive parenting in similar cultural and socioeconomic situations.